A comparison of dominance rank metrics reveals multiple competitive landscapes in an animal society. Issue 1934 (9th September 2020) - Levy, Emily J.; Zipple, Matthew N.; McLean, Emily; Campos, Fernando A.; Dasari, Mauna; Fogel, Arielle S.; Franz, Mathias; Gesquiere, Laurence R.; Gordon, Jacob B.; Grieneisen, Laura; Habig, Bobby; Jansen, David J.; et al.
Abstract : Across group-living animals, linear dominance hierarchies lead to disparities in access to resources, health outcomes and reproductive performance. Studies of how dominance rank predicts these traits typically employ one of several dominance rank metrics without examining the assumptions each metric makes about its underlying competitive processes. Here, we compare the ability of two dominance rank metrics—simple ordinal rank and proportional or 'standardized' rank—to predict 20 traits in a wild baboon population in Amboseli, Kenya. We propose that simple ordinal rank best predicts traits when competition is density-dependent, whereas proportional rank best predicts traits when competition is density-independent. We found that for 75% of traits (15/20), one rank metric performed better than the other. Strikingly, all male traits were best predicted by simple ordinal rank, whereas female traits were evenly split between proportional and simple ordinal rank. Hence, male and female traits are shaped by different competitive processes: males are largely driven by density-dependent resource access (e.g. access to oestrous females), whereas females are shaped by both density-independent (e.g. distributed food resources) and density-dependent resource access. This method of comparing how different rank metrics predict traits can be used to distinguish between different competitive processes operating in animal societies.